Environmentally friendly approach to postharvest quality maintenance of mango (Mangifera indica L.) cv. ‘Tommy Atkins’&‘Kent’ - Korsten, Lise (University of Pretoria, 2013)
Dissertation (MSc(Agric))--University of Pretoria, 2011.